Hysteresis in graphene nanoribbon field-effect devices - Tries, Alexander; Richter, Nils; Chen, Zongping; Narita, Akimitsu; Muellen, Klaus; Wang, Hai; Bonn, Mischa; Klaeui, Mathias (Physical Chemistry Chemical Physics, 2020)
Hysteresis in the current response to a varying gate voltage is a common spurious effect in carbon-based field effect transistors. Here, we use electric transport measurements to probe the charge transport in networks of armchair graphene nanoribbons with a width of either 5 or 9 carbon atoms, synthesized in a bottom-up approach using chemical vapor deposition. Our systematic study on the hysteresis of such graphene nanoribbon transistors, in conjunction with temperature-dependent transport measurements shows that the hysteresis can be fully accounted for by trapping/detrapping carriers in the SiO2 layer. We extract the trap densities and depth, allowing us to identify shallow traps as the main origin of the hysteresis effect.
CRIS-Team Scopus Importer:2023-03-27